Efficient Maturation and Cytokine Production of Neonatal DCs Requires Combined Proinflammatory Signals. Issue 2 (2005) - Krumbiegel, Doreen; Rohr, Jan; Schmidtke, Peter; Knuf, Markus; Zepp, Fred; Meyer, Claudius U.
Abstract : Specific functional properties of dendritic cells (DCs) have been suspected as being responsible for the impaired specific immune responses observed in human neonates. To analyze stimulatory requirements for the critical transition from immature, antigen-processing DCs to mature, antigen-presenting DCs, we investigated the effect of different proinflammatory mediators and antigens on phenotype and cytokine secretion of human neonatal DCs derived from hematopoietic progenitor cells (HPCs). Whereas single proinflammatory mediators were unable to induce the maturation of neonatal DCs, various combinations of IFNγ, CD40L, TNFα, LPS and antigens, induced the maturation of neonatal DCs documented by up-regulation of HLA-DR, CD83 and CD86. Combinations of proinflammatory mediators also increased cytokine secretion by neonatal DCs. Especially combined stimulation with LPS and IFNγ proved to be very efficient in inducing maturation and cytokine synthesis of neonatal DCs. In conclusion, neonatal DCs can be stimulated to express maturation as well as costimulatory surface molecules. However, induction of maturation requires combined stimulation with multiple proinflammatory signals.